2022
DOI: 10.31223/x5ks5h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The world’s second-largest, recorded landslide event: lessons learnt from the landslides triggered during and after the 2018 Mw 7.5 Papua New Guinea earthquake

Abstract: Widespread landslide events provide rare but valuable opportunities to investigate the spatial and size distributions of landslides in relation to seismic, climatic, geological and morphological factors. This study presents a unique event inventory for the co-seismic landslides induced by the February 25, 2018 Mw 7.5 Papua New Guinea earthquake as well as its post-seismic counterparts including the landslides triggered by either aftershocks or succeeding rainfall events that occurred between February 26 and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…In fact, our output could bring additional information on this topic supporting the scientific debate on landslide recovery (the time required for a given landscape to go back to pre-earthquake susceptibility conditions) by observing the predicted susceptibility change over time. Overall, multi-temporal landslide inventories and various associated parameters (e.g., number, size, area or volume of landslides) have already been used to explore landslide recovery in post-seismic periods (eg., Tanyas et al, 2021).…”
Section: Supporting Argumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, our output could bring additional information on this topic supporting the scientific debate on landslide recovery (the time required for a given landscape to go back to pre-earthquake susceptibility conditions) by observing the predicted susceptibility change over time. Overall, multi-temporal landslide inventories and various associated parameters (e.g., number, size, area or volume of landslides) have already been used to explore landslide recovery in post-seismic periods (eg., Tanyas et al, 2021).…”
Section: Supporting Argumentsmentioning
confidence: 99%
“…Slopes are also the same unit geotechnical solutions aim to address. Thus, an improvement to our ENN could involve moving away from a gridded spatial partition and towards more geomorphological-oriented mapping units such as slope units (Alvioli et al, 2016;Tanyaş et al, 2022b), sub-catchments or catchments (Shou and Lin, 2020;Wang et al, 2022).…”
Section: Opposing Argumentsmentioning
confidence: 99%
“…For this reason, response plots like Figure 7 add another level of understanding for they allow to monitor variations in SHAP with respect to each predictors' domain. This is a capability which is typical of statistical models (Lima et al, 2021;Tanyaş et al, 2022) and has found very few applications in machine learning (Park, 2015;Vorpahl et al, 2012). However, even in this case, the level of information provided is very generic and corresponds to the overall behaviour of each predictor with respect to the entire map it contributes to define.…”
Section: Discussionmentioning
confidence: 99%
“…The way they work is to assume a vector of landslide presence/absence data to behave across the geographic space according to a Bernoulli probability distribution, whose relation to the landslide is linearly related to a set of covariates. The latter are usually referred to as predisposing or triggering factors (Das et al, 2012;Tanyaş et al, 2022). However, the linearity assumption these models are based on, limited the performance one could obtain.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is common that a landslide area distribution is quite heavily tailed. In other words, the vast majority of inventories includes a predominant number of small landslides and only few extremely large ones, which is common in response to major triggering events, such as rainfall (Jones et al, 2021;Emberson et al, 2022) or earthquakes (Zhang et al, 2019;Tanyaş et al, 2022). This is the reason that has led Malamud et al (2004) to propose the Inverse Gamma distribution as a universal empirical size model, which lead to a series of studies on landslide Frequency Area Distribution (FAD; .…”
Section: Introductionmentioning
confidence: 99%